1997
DOI: 10.4319/lo.1997.42.7.1530
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen elimination in two deep eutrophic lakes

Abstract: Nitrogen elimination was investigated in two eutrophic Swiss lakes with different hypolimnetic oxygen conditions. Nitrogen burial was estimated from sediment-trap and sediment-core studies. Denitrification and NO, --ammonification rates were quantified with IsNO,-and acetylene incubation experiment! and whole-lake mass balances. The study confirmed earlier reports that the acetylene-block technique yields denitrification rates that are systematically too low. Denitrification rates obtained from isotope tracer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 36 publications
5
72
1
Order By: Relevance
“…The nearby eutrophic Lakes Baldegg (maximum depth 66 m) and Hallwil (maximum depth 47 m) have been similarly oxygenated and aerated since 1982 and 1986, respectively (Mengis et al 1997;Moosmann et al 2006). Before these remediation activities, the water columns of the latter two, nearly meromictic lakes were anoxic at depths .10 m during most of the year.…”
Section: Sites and Methodsmentioning
confidence: 99%
“…The nearby eutrophic Lakes Baldegg (maximum depth 66 m) and Hallwil (maximum depth 47 m) have been similarly oxygenated and aerated since 1982 and 1986, respectively (Mengis et al 1997;Moosmann et al 2006). Before these remediation activities, the water columns of the latter two, nearly meromictic lakes were anoxic at depths .10 m during most of the year.…”
Section: Sites and Methodsmentioning
confidence: 99%
“…A fraction of the dissolved NO 3 − may also be denitrified in the newly formed anaerobic sediments of the reservoir (e.g. Mengis et al, 1997;Friedl and Wüest, 2002). This may explain the lower concentrations of NO 3 − and DIP at…”
Section: Nutrients: N and Pmentioning
confidence: 99%
“…Nitrogen mass balance calculations show that the total net elimination of nitrogen in the South Basin amounted to 336 ϫ 10 3 kg N in 1999 (Table 2), corresponding to approximately 22% of the total nitrogen inventory. Net organic nitrogen burial generally does not contribute much to the total N removal in eutrophic lakes (e.g., Mengis et al 1997). For example, Meile (1996) has shown that, in the northern basin of Lake Lugano, N burial accounts for less than 13% of total annual N loss from this basin.…”
Section: Denitrification In the Deep Hypolimnion-the Distribution Of mentioning
confidence: 99%